Matthew's Transfiguration Story and Jewish-Christian Controversy. - Moses, A. D. (Library of New Testament studies., 1996)
The Gospel accounts of the transfiguration of Jesus continue to puzzle the average reader. The purpose of this book is to address some of the perplexing issues surrounding the event, and to explain the significance of the transfiguration, particularly in Matthew's Gospel. It demonstrates that Matthew's account of the event is to be seen in the context of first-century controversy between Christians and Jews about Jesus and Moses, with the Jews emphasizing Moses' greatness and Matthew portraying the transfiguration within Moses-Sinai categories and also in terms of the enigmatic Son of Man figu.